Reduction in non-abstinent World Health Organization (WHO) drinking risk levels and drug use disorders: 3-year follow-up results in the US general population. (1st August 2019) - Knox, Justin; Wall, Melanie; Witkiewitz, Katie; Kranzler, Henry R.; Falk, Daniel E.; Litten, Raye; Mann, Karl; O'Malley, Stephanie S.; Scodes, Jennifer; Anton, Raymond; Hasin, Deborah S.; ,
Highlights: In heavy drinkers drinking reductions decreased the risk of drug use disorder. WHO drinking risk level reductions are useful indicators of how individuals feel. WHO risk level reductions are useful indicators of clinical benefit. Abstract: Background: To provide information on the clinical relevance of a reduction in the World Health Organization (WHO) drinking risk categories, we examined their relationship to an important indicator of how individuals feel and function: drug use disorders (DUDs), i.e., those involving substances other than alcohol. Method: Current drinkers in a U.S. national survey (n = 22, 005) were interviewed in 2001-02 and re-interviewed 3 years later. WHO drinking risk levels and DSM-IV-defined DUD were assessed at both waves. The relationship of changes in WHO drinking risk levels to the presence of DUD were examined using adjusted odds ratios (aOR). Results: At Wave 1, 2.5% of respondents were WHO very-high-risk drinkers, and 2.5%, 4.8%, and 90.2% were high-risk, moderate-risk, and low-risk drinkers, respectively. Among Wave 1 very-high-risk drinkers, significantly lower odds of DUD at Wave 2 were predicted by reductions in WHO risk levels of one, two or three levels (aOR = 0.15, 0.01, 0.24, respectively; all p-values <.0001). Among participants who initially were drinking at lower risk levels, reductions in drinking or abstinence were generally associated with significantly lower odds of DUD, although the results were less consistent. Conclusions: Among very-high-risk drinkers, reduction in the WHO drinking risk categories were associated with lower risk of a DUD. These results add to findings indicating that reductions in WHO drinking risk levels are a meaningful indicator of how individuals feel and function and could therefore serve as informative outcomes in alcohol clinical trials. WHO risk levels can also guide treatment goals and clinical recommendations on drinking reduction.